The City in Cinema: Referenciality throughout the Filming Stages - Caldevilla-Domínguez, David; Barrientos-Báez, Almudena; Blanco-Pérez, Manuel (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2022)
The Western Euro project had its element of referentiality in the languages ​​of modernity. In Metropolis (Fritz Lang, 1927), the future dystopian city was designed, turning the big screen into an element of reference. But World War II started a bankruptcy on that regenerationist principle. Consumerism endangered the city-country balance. Through a film analysis, we propose a study of three films, from which the city is shaped as a reference from the human to the inhuman, from the collective to the new consumerist citizen. Showing how we have changed our perception of cities due to their interpretation in the cinema.